KARAKTERISASI BERDASARKAN UJI ASPEK MORFOLOGI DAN BIOKIMIA SERTA PENGARUH AERASI TERHADAP PERTUMBUHAN Zymomonas mobilis GALUR LIAR (ZM JPG) - Teta Mumtaz Kurniasari; Surya Rosa Putra (Molluca Journal of Chemistry Education (MJoCE), 2011)
Zymomonas mobilis is a facultative anaerobic bacteria that have the characteristics of a gram-negative rodshaped, oxidase test negative, positive catalase test, did not form indol and did not hydrolyze gelatin. Some other characteristics such as motility, formation of H2S, and the levels of tolerance to oxygen varies between strains result Z. mobilis. Z. mobilis ZM JPG collection ITS laboratory tested chemical and morphological aspects of the biochemical aspects. The test results stated that ZM JPG have the characteristics of a rod-shaped gramnegative, facultative anaerobic, form round colonies, colony edges intact, convek and white. JPG ZM are motile, can not grow on lactose and mannitol, glucose and sucrose can menfermentasi, negative oxidase test, catalase test positive, does not form H2S and do not form indol. ZM JPG able to grow on media with glucose concentration of 100 g / l. Lag phase lasted for 5 hours in both media aerated or not aerated. Slowed growth phase in a shorter aerated media that is 3 hours, while the media is not aerated lasts for 8 hours. Optimum growth is achieved on a 34-hour incubation in both media aerated or not aerated